Prevalence of insomnia and poor sleep quality in the prison population: A systematic review. (5th July 2022) - Sheppard, Nia; Hogan, Lee
Summary: Insomnia is a public health concern with several associated negative health‐related outcomes. Risk factors for insomnia place the prison population at an increased risk of inadequate sleep. This paper systematically reviewed the literature reporting on the prevalence of insomnia and poor sleep quality in the prison population. Following a comprehensive database search and screening process, 12 studies were eligible for inclusion in this review. Six studies provided prevalence rates for insomnia and nine for poor sleep quality. Varied prevalence rates were found for insomnia (i.e. 26.2%–72.5%) and poor sleep quality (i.e. 42.8%–88.2%). Evaluation of the prevalence rates revealed varied measurement of sleep quality, inconsistent parameters of standardised measures, and methodological heterogeneity. Other considerations were given to geographical differences, the use of self‐report data, gender difference, environmental factors and comorbidities of insomnia. The review highlighted an increase in the quantity of studies and some improved quality; although the findings were highly variable, in the main, inadequate sleep amongst prisoners was higher than the general population. Limitations of the review and implications for further research are discussed.